Deformation Analysis of the Main Components in a Single Screw Compressor. Issue 1 (July 2015) - Liu, Feilong; Liao, Xueli; Feng, Quanke; Van Den Broek, Martijn; De Paepe, Michel
Abstract: The single screw compressor is used in many fields such as air compression, chemical industry and refrigeration. During operation, different gas pressures and temperatures applied on the components can cause different degrees of deformation, which leads to a difference between the thermally induced clearance and the designed clearance. However, limited research about clearance design is reported. In this paper, a temperature measurement instrument and a convective heat transfer model were described and used to establish the temperature of a single screw air compressor's casing, screw rotor and star wheel. 3-D models of these three main components were built. The gas force deformation, thermal- structure deformation and thermal-force coupling deformation were carried out by using a finite element simulation method. Results show that the clearance between the bottom of the groove and the top of star wheel is reduced by 0.066 mm, the clearance between the side of groove and the star wheel is reduced by 0.015 mm, and the clearance between the cylinder and the rotor is reduced by 0.01 mm. It is suggested that these deformations should be taken into account during the design of these clearances.